Web-Based Business Simulation Practice Course Learning Application - Jumjuma Jumjuma; Agus Mariani Saragih; Enda Surbakti; Lily M Nasution; Fivi Rahmatus Sofiyah (Jurnal Penelitian Pendidikan IPA, 2023)
This research is planned to continue and realize the results and objectives of previous research in 2022 with applied research on innovative products, namely Practical Learning Applications for Virtual Business Simulation Courses in the Business Administration Study Program. The long-term goal of this research is to develop project-based and digital technology-based Business Simulation learning courses used by students and lecturers. The method used to achieve this is the R and D method. The target for this research output is Copyright and publication of the accredited national journal Sinta 2. This research produces a virtual business simulation learning application based on a research model that was created in 2022. Research This is a type of action research and development using the Research and Development (R&D) method. This research also tested innovative products practiced by 70 5th-semester students, 10 people were taken from each 5th-semester class of the Business Administration Study Program (7 classes) as test respondents in using this Business Simulation application. The Business Simulation Application was created under the business simulation learning process contained in the RPS for the Business Simulation Course. This simulation application is web-based and is equipped with a video tutorial to make it easier to use. Application testing results show that this business simulation application makes business work easier and faster for the positions of manager, head of administrative supplies, and head of finance.